The Narrative and the Symbolic Construction of Nation in Lithuania in 1988-1991 - Klumbytė, Neringa (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is to analyze the narratives and the symbols of Lithuanian Sąjūdis (1988-1991). The narratives and the symbols played an important role in building the nation, defined through the symbols such as the ‘West’ and the ‘East’, ‘democracy’, ‘civil society’ on the one hand and the historical memory on the other. The article discusses their role on the level mobilizing the movement, constructing the idea of the nation and justifying the social and political change. The analysis of symbols, narratives reveals the remaining importance of the idea of socialism in the period of the movement.